The Effect of Reading Interest and Motivation on Student Learning Outcomes at SDN 06 Kisam Tinggi, Kisam Tinggi District - Ariyes, Ilham; Fitria, Happy; Puspita, Yenny (LPPM Universitas Pahlawan Tuanku Tambusai, Riau, Indonesia, 2021)
This study aims to determine and analyze the magnitude of the influence of reading interest and reading motivation together on student learning outcomes of SDN 06 Kisam Tinggi. Research to be carried out includes quantitative research. The research method is a scientific procedure or way to obtain data with a specific purpose. Descriptive research is research that uses observations, interviews or questionnaires regarding the current situation. The conclusion that can be drawn from the results of research and discussion is that there is a positive and significant effect of reading interest on student learning outcomes at SDN 06 Kisam Tinggi. The results of calculations using simple regression analysis show that the correlation coefficient is 0.327 and the coefficient of determination is 1.107. There is a positive and significant effect of learning motivation on student learning outcomes at SDN 06 Kisam Tinggi.